Literature survey on manufacturing alumina/aluminum MMC by stir casting and their wear behaviors with and without solid lubrication - Md Idriss, A. N.; Kasolang, S.; Maleque, Md. Abdul (Springer, 2022)
Alumina (Al2O3) particles are used to incorporate into the aluminum either through liquid, semi liquid or solid-state processing condition because they could provide, high strength, high modulus, and hardness properties com-pared to those without the reinforcement. Some major problems such as wettability, porosity, and poor dispersion of particles from the view of processing conditions to produce the aluminum metal matrix composites are brought forward in this paper with several techniques for improvising. Many works had shown success of mitigating wear through the incorporation of alumina into aluminum with several degree of weight losses, depending on the produced composites properties. These, however, are still considered high when compared to those with the incorporation of solid lubricant such as carbon nanotube (CNT) or graphite which is our major concern for future development. This paper reviews several aspects that are needed during stir casting upon mixing the alumina particulates with the molten aluminum and so when solid lubricants are added. This paper is also aimed to provide a preliminary and specific guide for a researcher to initiate an experimental work, tailoring a niche area in alumina-aluminum metal matrix composite fabrication and wear testing by adjusting the angle of deposition to 45°, the improved coatings can be achieved especially at the uneven threat part of the bolt. The hardness was also found to be higher at the alignment of 45° angle. Keywords: Stir casting · Alumina · SiC · Aluminum · Metal matrix composite · Wear